Formation of milk lipids: a molecular perspective - McManaman, James L (Clin Lipidol, 2009)
Lipids, primarily triglycerides, are major milk constituents of most mammals, providing a large percentage of calories, essential fatty acids and bioactive lipids required for neonatal growth and development. To meet the caloric and nutritional demands of newborns, the mammary glands of most species have evolved an enormous capacity to synthesize and secrete large quantities of lipids during lactation. Significant information exists regarding the physiological regulation of lipid metabolism in the mammary gland from the study of dairy animals. However, detailed understanding of the molecular mechanisms regulating milk lipid formation is only now coming into focus through advances in mouse genetics, global analysis of mammary gland gene expression, organelle protein properties and the cell biology of lipid metabolism.